2023
DOI: 10.3390/en16186431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Progress of Renewable Energy Sources in Poland: A Multidimensional Analysis

Stanisław Jaworski,
Mariola Chrzanowska,
Monika Zielińska-Sitkiewicz
et al.

Abstract: Energy is a key driver of all modern economies. Sustainable development is playing an increasingly important role both at regional and local levels. It is a compromise between social and economic needs and the preservation of nature. In the policy of the European Union, the idea of sustainable development and environmental protection is of decisive importance for the implemented programs and economic activities. Contemporary challenges require the transformation of the energy market towards greater use of rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The increase in energy demand [3], the implementation of the European Union's climate and energy policy [4,5], and recent political events (the war in Ukraine) have been a verifier of the importance of energy policy. The countries' authorities observed that moving the power generation model from central to distributed with energy storage is preferable.…”
Section: Development Of Photovoltaic Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in energy demand [3], the implementation of the European Union's climate and energy policy [4,5], and recent political events (the war in Ukraine) have been a verifier of the importance of energy policy. The countries' authorities observed that moving the power generation model from central to distributed with energy storage is preferable.…”
Section: Development Of Photovoltaic Projectsmentioning
confidence: 99%
“…Energy production from natural sources, for example, from the sun, is one of the realizations of the green economy. It is a response to ongoing climate change [3][4][5], capable of paying off in the long term [6].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, Poland has paid increasing attention to investments in renewable energy sources as an alternative to traditional ones that burn fossil fuels, which contribute to environmental pollution and climate change [10][11][12][13]. The future of renewable energy in Poland after 2020 seems promising due to the growing interest in this form of energy from both the state authorities, the public, and investors [14][15][16].…”
Section: Goals and Directions Of Renewable Energy Investments In Polandmentioning
confidence: 99%
“…There is no doubt that building a low-emission and resource-efficient economy whose priority is environmental protection in the face of the depletion of conventional energy sources is desirable [33][34][35][36][37][38]. Researchers indicate that the production of renewable energy helps reduce a country's energy dependence [39][40][41]. This aspect is of strategic importance for many world economies, also due to the Russian-Ukrainian war (read more [42][43][44]).…”
Section: Reasons For Increasing the Use Of Renewable Energy Sourcesmentioning
confidence: 99%